2001
DOI: 10.1128/aac.45.12.3445-3450.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interactions between Nelfinavir and 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase Inhibitors Atorvastatin and Simvastatin

Abstract: 3-Hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors are effective agents in lowering cholesterol and triglycerides and are being used by human immunodeficiency virus-positive patients to treat the lipid elevation that may be associated with antiretroviral therapy. Many HMG-CoA reductase inhibitors and protease inhibitors are metabolized by the same cytochrome P450 enzyme 3A4 (CYP3A4). In addition, many protease inhibitors are potent inhibitors of CYP3A4. Therefore, coadministration of these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(59 citation statements)
references
References 25 publications
1
55
2
1
Order By: Relevance
“…39 Co-administration of simvastatin and lovastatin with protease inhibitors may significantly increase serum levels of the statin, resulting in potential myopathy, including rhabdomyolysis. 40,41 In contrast to the results of our study, the Swiss HIV Cohort Study found that only 2 % of their patients had been prescribed contraindicated ARV/non-ARV combinations, which largely involved midazolam, 35 while 59 % had been prescribed ARV/ non-ARV combinations that were not contraindicated, yet had interactions requiring potential dose adjustment and/or close monitoring. The differences between our observations and those of the Swiss HIV Cohort Study scientists may be explained at least in part by their use of a customized version of the Liverpool database, use of different definitions for important but not contraindicated interactions, and their review of all interactions by two pharmacists.…”
Section: Discussioncontrasting
confidence: 53%
“…39 Co-administration of simvastatin and lovastatin with protease inhibitors may significantly increase serum levels of the statin, resulting in potential myopathy, including rhabdomyolysis. 40,41 In contrast to the results of our study, the Swiss HIV Cohort Study found that only 2 % of their patients had been prescribed contraindicated ARV/non-ARV combinations, which largely involved midazolam, 35 while 59 % had been prescribed ARV/ non-ARV combinations that were not contraindicated, yet had interactions requiring potential dose adjustment and/or close monitoring. The differences between our observations and those of the Swiss HIV Cohort Study scientists may be explained at least in part by their use of a customized version of the Liverpool database, use of different definitions for important but not contraindicated interactions, and their review of all interactions by two pharmacists.…”
Section: Discussioncontrasting
confidence: 53%
“…To counter this, statins are often administered to these individuals to reduce cholesterol and triglyceride levels (42). However, coadministration of retroviral protease inhibitor and statins has now been shown to increase several fold the peak concentrations of statins in the plasma (43)(44)(45). Whether this abnormally high concentration of statins in the plasma of HIV patients will result in any inflammatory response is not known and deserves further attention.…”
Section: Discussionmentioning
confidence: 99%
“…This interindividual variability may be caused by the fact that atorvastatin is supposed to inhibit HMG-CoA reductase in the liver, so the systemic levels of this lipophilic compound vary considerably between individuals. 12 Extending our data to the clinical situation, the differential response of the volunteers suggests that individual patients will benefit to different degrees from the pleiotropic effects of statins, independently of the lipid-lowering effect. The increase in nonisoprenylated inactive form of RhoA in PBMCs has been linked to the atheroprotective effects of statins on these cells, such as downregulation of plasminogen activator inhibitor-1 synthesis, 18 decreased transcription of matrix metalloproteinases and adhesion molecules in monocytes, 16 decreased monocyte-endothelial cell interactions, 23 and inhibition of activation and proliferation of T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%